Operational radiation safety considerations during superficial x-ray treatment for veterinary applications - Singh, Ashutosh, author; Leary, Del, advisor; Johnson, Thomas, advisor; Wotman, Kathryn, committee member (Colorado State University. Libraries, 2021)
This study was conducted to determine whether the scatter x-ray emission during a superficial radiation treatment (SRT) using the SRT-100™ result in a significant occupational dose to veterinary personnel present in the room during treatment. Measurements were taken for 50, 70, and 100 kV x-ray for 9 different SRT-100 applicators. The exposure rates at the surface of solid water phantom (SWP) phantom ranged from 3.9 mR/hr for applicator #2 to 396 mR/hr for CB18 for 50 kV, from 41 mR/hr to 2,880 mR/hr for 70 kV, and from 235 mR/hr to 7,500 mR/hr, for 100 kV, respectively. A heat map of scatter x-ray around the x-ray source was generated for 50, 70, and 100 kV at 25 cm and 75 cm above the SWP surface plane. The highest measured exposure rate was at 0.5 m from the applicator and was 76.8 mR/hr at 25 cm above SWP and 33.6 mR/hr at 75 cm above the SWP for 50 kV. Exposure rate values at same locations were 192 mR/hr and 96 mR/hr for 70 kV, and 389 mR/hr and 194 mR/hr for 100 kV, respectively. A horse phantom was utilized to generate a spatial dose profile at 1m for 50, 70, and 100 kV and it was discovered that backscatter emission has an angular response. Residence time for veterinary staff to exceed 10% of quarterly dose limits were calculated for 50, 70, and 100 kV and distances ranging from 0.5m to 2.5 m. These values ranged from a minimum of 24 min for 100 kV at 0.5m to a maximum of 7,813 min for 50 kV at 2.5 m. Minimum distance from the applicator for exposure rates below 2 mR/hr were calculated to be 1.78, 2.52, and 3.45 m, for 50, 70, and 100 kV, respectively.